Boron in Catalysis and Materials Chemistry: A Themed Issue in Honor of Professor Todd B. Marder on the Occasion of His 65th Birthday - Kakkar, Ashok (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Boron, a metalloid with rich chemistry, continues to offer a diverse platform in designing novel catalysts and materials for applications in a variety of areas. This book, while celebrating Professor Todd Marder's contributions to boron chemistry, on the occasion of his 65th birthday in November 2020, highlights and brings into focus some of the important discoveries in this field, through state-of-the-art reviews and research articles